Penerapan Protokol Keselamatan Pasien Di Post-Anesthesia Care Unit (PACU) Terhadap Penurunan Insiden Komplikasi Pascaanestesi: Scooping - Zulfikar , Rexa Irfanul Hakim; Kalista, Zalva; ., Resviana; Widyatama, Amrunafi; Pramita, Ellyda Septiani (CV. ITTC INDONESIA, 2026)
Patient safety in the Post-Anesthesia Care Unit (PACU) is a critical aspect of postoperative care due to the high risk of complications caused by residual anesthetic effects. This scoping review aims to map scientific evidence regarding the implementation of patient safety protocols in PACU and their contribution to reducing post-anesthetic complications. Literature searches were conducted through PubMed, Scopus, ScienceDirect, SpringerLink, and Google Scholar databases for articles published between 2020 and 2025. Ten relevant studies met the inclusion criteria and were analyzed narratively. The findings indicate that the implementation of patient safety protocols based on American Society of Anesthesiologists (ASA) and Association of Anaesthetists of Great Britain and Ireland (AAGBI) standards significantly reduces complications such as hypothermia, postoperative nausea and vomiting, hypoxia, and hemodynamic instability by approximately 40–50%. Continuous monitoring, nurse compliance with standard operating procedures, adequate facilities, and multidisciplinary collaboration are key factors influencing successful protocol implementation. This review highlights that consistent application of patient safety protocols in PACU improves patient outcomes and supports the development of evidence-based nursing practice in anesthesia care.